THE EFFECTS OF BRAND IMAGE, BRAND SATISFACTION, AND BRAND TRUST ON LOYALTY FORMATION: THE MODERATION ROLE OF BRAND LOVE AND BRAND RESPECT OF MIXUE ICE CREAM & TEA - Hilda Zulfa Hayuni; Osa Omar Sharif (Jurnal Ekonomi, 2023)
Trends in the beverage industry in Indonesia continue to develop at an increasingly positive and interesting pace to study. Consumers have long-term relationships with food and beverage brands, but are not reluctant to switch when trust declines due to poor product quality, price increases, and irrelevance. Mixue is in the middle of a hyper-competitive market and must be able to gain customer loyalty. This research is expected to be able to reveal the relationship and the significant effects of brand image, brand satisfaction, and brand trust on brand loyalty through the moderator variables of Lovemarks (brand love and brand respect). The approach used is quantitative and causal using online surveys through questionnaires on Google Forms and data processing using SPSS and SmartPLS 3.2.9. Based on the results of data analysis, it was found that there was a significant and positive influence obtained from the relationship between brand image on brand satisfaction and brand trust, brand satisfaction on brand trust, brand satisfaction and brand trust on brand loyalty, and moderation of brand love on brand satisfaction and brand loyalty relationships. . Meanwhile, the moderating effect on the relationship between other variables did not occur significantly. Suggestions from this study are that Mixue Ice Cream and Tea is expected to be able to maintain and strengthen marketing efforts, improve the quality of its products and services, increase emotional bonds and provide pleasant experiences.